Partial computerization of purchase system in Sysmech Automation Pte Ltd - Wong, Virginia Wai Yin (2015)
The major focus of most papers in the past had been confined to the computerization of accounting systems. Few studies attempted to examine the computerisation of purchasing systems in manufacturing firms. Sysmech Automation, operating in Singapore is chosen for this study because one of the authors worked at the company during her business attachment. It is a medium sized manufacturing company with a manual purchasing system. This study attempts to examine the requirements, problems and solutions of the computerization of a manual purchasing system. The methodology used is the Systems Development Life Cycle (SDLC). The focus of the study is systems analysis and general design. However, the other phases will be briefly mentioned. A recommendation is given, based on the SDLC, which would satisfy most of the needs of the end users.